Less Is More: Lowering Cattle Stocking Rates Enhances Wild Herbivore Habitat Use and Cattle Foraging Efficiency - Wells, Harry B. M.; Crego, Ramiro D.; Ekadeli, Jackson; Namoni, Mathew; Kimuyu, Duncan M.; Odadi, Wilfred O.; Porensky, Lauren M.; Dougill, Andrew J.; Stringer, Lindsay C.; Young, Truman P. (Frontiers in Ecology and Evolution, 2022)
Over a quarter of the world’s land surface is grazed by cattle and other livestock, which are replacing wild herbivores and widely regarded as drivers of global biodiversity declines. The effects of livestock presence versus absence on wild herbivores are well documented. However, the environmental context-specific effects of cattle stocking rate on biodiversity and livestock production are poorly understood, precluding nuanced rangeland management recommendations. To address this, we used a long term exclosure experiment in a semi-arid savanna ecosystem in central Kenya that selectively excludes cattle (at different stocking rates), wild mesoherbivores, and megaherbivores. We investigated the individual and interactive effects of cattle stocking rate (zero/moderate/high) and megaherbivore (> 1000 kg) accessibility on habitat use (measured as dung density) by two dominant wild mesoherbivores (50-1000 kg; zebra Equus quagga and eland Taurotragus oryx) across the ‘wet’ and ‘dry’ seasons. To explore potential tradeoffs or co-benefits between cattle production and wildlife conservation, we tested for individual and interactive effects of cattle stocking rate and accessibility by wild mesoherbivores and megaherbivores (collectively, large wild herbivores) on the foraging efficiency of cattle across both seasons. Eland habitat use was reduced by cattle at moderate and high stocking rates across both dry and wet seasons and regardless of megaherbivore accessibility. We observed a positive effect of megaherbivores on zebra habitat use at moderate, but not high, stocking rates. Cattle foraging efficiency (g dry matter step-1 min-1) was lower in the high compared to moderate stocking rate treatments during the dry season, and was non-additively reduced by wild mesoherbivores and high cattle stocking rates during the wet season. These results show that high stocking rates are detrimental to wild mesoherbivore habitat use and cattle foraging efficiency, while reducing to moderate stocking rates can benefit zebra habitat use and cattle foraging efficiency. Our findings demonstrate that ecosystem management and restoration efforts across African rangelands that involve reducing cattle stocking rates may represent a win-win for wild herbivore conservation and individual performance of livestock.